BUDIDAYA IKAN NILA MENGGUNAKAN KOLAM TERPAL SEBAGAI WADAH DALAM MENDUKUNG KETAHANAN PANGAN DI DESA SUKAMANAH KABUPATEN PANDEGLANG - Muhamad Sunarya; Tabroni Tabroni; Masnun Masnun; Alif Dwi Rahmawati; Depi Febriansyah (Yayasan Education and Social Center, 2021)
Tarp-typed pond or tarpaulin pond is an appropriate medium for cultivation of Nile tilapia because of its many advantages including (1) easily moved from one place to another,(2) friendly toward soil construction, (3) suitable with tilapia’s characteristics and (4) very convenient forcleaning and harvesting. This community service focused on societal groups in Tariang Lama Village, Kendahe district whose society normally have difficulty in obtaining fish during stormy sea. This community service consisted of (1) field survey, (2) mentoring, (3) training and (4) evaluation/monitoring. The targeted societal groups in Tariang Lama were already capable of designing, building their own tarp-typed pool and cultivating Nile tilapia with tarpaulin pond. In addition, evaluation and monitoring showed that the people of Tariang Lama had no problem in adopting fish cultivation technique with tarpaulin pond. Many of them even designed and built their own tarp-typed pond, strongly suggesting the openness and acceptance of the people of Taring Lama towards the implementation of the relatively new fish farming technique